Vacuum–Sublimable Ionic Yellow Phosphorescent Iridium(III) Complexes with Broad Emission for White Electroluminescence - Peng Tao (Wiley-VCH, 2021)
The exploration of efficient yellow emitters featuring broad emission band plays an essential role for the complementary‐color‐based white organic light‐emitting devices (OLEDs). Herein, two new yellow ionic iridium(III) complexes (Ir1 and Ir2) having excellent sublimation ability are designed and prepared by the incorporation of chlorine‐modified 2‐phenylquinoline ligand and introduction of bulky counter ion. At room temperature, these ionic iridium(III) complexes show bright yellow phosphorescence in both solid and solution states due to the presence of bulky counter ion. They share the same emission wavelength (538 and 573 nm as the emission shoulder) with extremely high quantum yields (as high as 0.91) in Ar‐saturated CH2Cl2. Notably, those complexes also exhibit very broad full width at half maximum (FWHM) (up to 100 nm) attributed to almost the same intensities of emission maximum and shoulder, making them excellent candidates for white electroluminescence. The as‐prepared yellow OLEDs show high external quantum efficiency (EQE) of 11.6% and broad FWHM of 105 nm. The two‐color‐based white OLED is prepared with peak EQE of 9.2%, the 1931 CIE coordinate of (0.29, 0.31), and color rendering index of 79, proving that these new ionic iridium(III) complexes show a great potential for white electroluminescence.